SOFT SKILLS ASSESSMENT DURING RECRUITMENT PROCESS IN RECRUITER'S OPINION - Michał Tomczak (Research on Enterprise in Modern Economy Theory and Practice, 2015)
The main problem of this article is a try to explore the way that recruiters consider candidates performance during recruitment process, their competences, “soft skills”, what features they find as valuable and which selection methods currently are the most popular. Empirical part of text is based on data gained from qualitative research, concretely from an interview carried out among professional recruiters who participate in candidates selection process in companies.